Interfacial tension reduction mechanism by alkaline-surfactant-polymer at oil-water interface from experimental and molecular dynamics approaches - Numin, M.S. (Elsevier B.V., 2022)
Chemical injection such as alkaline (A), surfactant (S), and polymer (P) in chemical enhanced oil recovery (CEOR) can improve oil recovery by modifying the injected fluid characteristics to enhance interaction with oil in the reservoir. The presence of complex composition in CEOR flooding complicates the study in investigating the mechanism of ASP at the oilâwater interface. For this reason, the interfacial tension (IFT) reduction mechanism of ASP solution with the presence of crude oil was investigated via experimentally and molecular dynamics (MD) simulation. The IFT analysis was conducted to determine the optimum ASP composition in reducing the IFT value. The spinning drop video tensiometer (SVT) was used to measure the IFT experimentally. The optimum composition of ASP in reducing the IFT value was 0.3 M S672, 1.0 M Na2CO3, and 0.125 ÂµM hydrolyzed polyacrylamide (HPAM) solution with the IFT value of 0.08 mN/m. The MD simulation successfully predicted the mechanism of ASP in reducing the IFT value. The mechanism in IFT reduction was explained by the surfactant adsorption at the interface, interfacial thickness, and hydrogen bond formation. Â© 2022 Elsevier B.V.